COMPARISON OF AZTREONAM AGAINST OTHER ANTIBIOTICS USED IN URINARY TRACT INFECTIONS - Khan, Muhammad Tariq; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 2001)
Background: Urinary tract infection is a very common problem in adults as well as in children. There is always need for the right antibiotic to be chosen for treatment. Methods: This study was conducted at Microbiology section in Pathology department of Ayub Medical College, Abbottabad, Pakistan. In this study the aztreonam which is only effective against gram negative bacilli has been compared with other conventionally used antibiotics, ampicillin, cotrimoxazole, minocycline, pipemedic acid, nalidixic acid, norfloxacin, ciprofloxacin, gentamicin and ceftriaxone. Results: Total gram negative isolates were 342. Out of this 76.6% (262) were E.coli. Klebsiella pneumoniae 14.3% (49), proteus species 5.2%(I8) and pseudomonas aeruginosa were 3.8% (13). The aztreonam showed 78% sensitivity against gram negative bacilli which is better than norfloxacin which showed 62.2% sensitivity.